(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Present study presents a cunning cross variety methodology, explicitly ’Fractional Summarized Homotopy Assessment Procedure’ (FGHAM) which is made by uniting the fractional auxiliaries in the summarized crucial transform strategy. The fractional summarized fundamental transform method and the Homotopy examination method are utilized to deal with fractional solicitation nonlinear differential equations. For various groups of nonlinear fractional differential equations, including the Navier-Woods-Ups model and the Riccati equations, the proposed system performs poorly. The cross assortment system, in contrast to the other fast methods, provides a comprehensive method for controlling the intermixing region of the assisted series arrangement through a collaboration with a limit of h. Additionally, as proposed in this paper, the FGHAM near the various models reveals that this strategy can be effectively used as a device for dealing with a variety of nonlinear fragmentary differential conditions.